I Am Ok You Are Ok - Thomas A Harris (Avon, 1969)
\Happy childhood\ notwithstanding, most of us are living out the NOT OK feelings of a defenseless CHILD wholly dependent on OK others for stroking and care. By the third year of life, says Dr. Harris, most of us have made the unconscious decision I\'M NOT OK-YOU\'RE OK. This negative Life Position, shared by successful and unsuccessful people alike, contaminates our rational ADULT potential -- leaving us vulnerable to the inappropriate, emotional reactions of our CHILD and the uncritically learned behavior programmed into our PARENT.In personal Transactions, NOT OK people resort to harmful withdrawal, rituals, activities, pastimes, and games for getting needed strokes while avoiding painful intimacy with people they see as OK.Dr. Thomas A. Harris\'s pioneering work in Transactional Analysis has had a fundamental impact on our understanding of interpersonal behavior. In showing us how to make the conscious decision I\'M OK-YOU\'RE OK, he has helped millions of despairing people find the freedom to change, to liberate their ADULT effectiveness, and to achieve joyful intimacy with the people in their lives.